How Reliable are Patient‐Reported Rehospitalizations? Implications for the Design of Future Practical Clinical Studies. Issue 1 (January 2016) - Krishnamoorthy, Arun; Peterson, Eric D.; Knight, J. David; Anstrom, Kevin J.; Effron, Mark B.; Zettler, Marjorie E.; Davidson‐Ray, Linda; Baker, Brian A.; McCollam, Patrick L.; Mark, Daniel B.; Wang, Tracy Y.
Abstract : Background: Longitudinal clinical investigations often rely on patient reports to screen for postdischarge adverse outcomes events, yet few studies have examined the accuracy of such patient reports. Methods and Results: Patients with acute myocardial infarction (MI) in the TRANSLATE‐ACS study were asked during structured interviews at 6 weeks, 6 months, and 12 months postdischarge to report any rehospitalizations. The accuracy of patient‐reported rehospitalizations within 1 year of postdischarge was determined using claims‐based medical bill validation as the reference standard. The cumulative incidence of rehospitalizations was compared when identified by patient report versus medical bills. Patients were categorized by the accuracy in reporting events (accurate, under‐, or over‐ reporters) and characteristics were compared between groups. Among 10 643 MI patients, 4565 (43%) reported 7734 rehospitalizations. The sensitivity and positive predictive value of patient‐reported rehospitalizations were low at 67% and 59%, respectively. A higher cumulative incidence of rehospitalization was observed when identified by patient report versus medical bills (43% vs 37%; P <0.001). Overall, 18% of patients over‐reported and 10% under‐reported the number of hospitalizations. Compared with accurate reporters, under‐reporters were more likely to be older, female, African American, unemployed, or a non‐high‐school graduate, and had greater prevalence of clinical comorbidities such as diabetes and past cardiovascular disease. Conclusions: The accuracy of patient‐reported rehospitalizations was low with patients both under‐ and over‐reporting events. Longitudinal clinical research studies need additional mechanisms beyond patient report to accurately identify rehospitalization events. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT01088503.